2021
DOI: 10.1038/s41598-020-80301-5
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional transformation of chemical bonding during crystallization in a layered chalcogenide material

Abstract: Two-dimensional (2D) van der Waals (vdW) materials possess a crystal structure in which a covalently-bonded few atomic-layer motif forms a single unit with individual motifs being weakly bound to each other by vdW forces. Cr2Ge2Te6 is known as a 2D vdW ferromagnetic insulator as well as a potential phase change material for non-volatile memory applications. Here, we provide evidence for a dimensional transformation in the chemical bonding from a randomly bonded three-dimensional (3D) disordered amorphous phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The buckling of the layers may be attributable to the positional and compositional disorder that still exists during the initial stages of crystallization into a 2D layered structure. We note here that a similar process, namely, the formation of the layered structure with the remaining local disorder, was also observed during the crystallization of a different 2D chalcogenide Cr 2 Ge 2 Te 6 , , suggesting that this may be a typical feature of a 3D–2D crystallization process.…”
Section: Resultssupporting
confidence: 70%
“…The buckling of the layers may be attributable to the positional and compositional disorder that still exists during the initial stages of crystallization into a 2D layered structure. We note here that a similar process, namely, the formation of the layered structure with the remaining local disorder, was also observed during the crystallization of a different 2D chalcogenide Cr 2 Ge 2 Te 6 , , suggesting that this may be a typical feature of a 3D–2D crystallization process.…”
Section: Resultssupporting
confidence: 70%
“…The crystallization speed for amorphous CrGT is as fast as that of GST, but there is the possibility that the time duration of 40 ns is not sufficient for the molten CrGT to completely transform to high-resistive crystalline phase, leading to a residual metastable phase in the set state. Amorphous CrGT has been reported to crystallize to a high-resistive crystalline phase via the low-resistive metastable phase. , Recent studies have revealed that the metastable phase shows long-range order and short-range disorder. , Because of these unique structural features, the physical properties of the metastable phase have not been sufficiently investigated. To incorporate the influence of the metastable phase, the temperature dependence of σ was measured for the 290 °C-annealed film, which is reported as metastable CrGT. , To verify this influence, we assumed that the metastable phase is formed above the amorphous region with a thickness t of 7 nm, which is equivalent to the range between the amorphous surface and T max point or 77 nm, which is equivalent to the distance between the amorphous surface and the farthest point reaching T m from the electrode (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Amorphous CrGT has been reported to crystallize to a high-resistive crystalline phase via the low-resistive metastable phase. , Recent studies have revealed that the metastable phase shows long-range order and short-range disorder. , Because of these unique structural features, the physical properties of the metastable phase have not been sufficiently investigated. To incorporate the influence of the metastable phase, the temperature dependence of σ was measured for the 290 °C-annealed film, which is reported as metastable CrGT. , To verify this influence, we assumed that the metastable phase is formed above the amorphous region with a thickness t of 7 nm, which is equivalent to the range between the amorphous surface and T max point or 77 nm, which is equivalent to the distance between the amorphous surface and the farthest point reaching T m from the electrode (Figure S5). Since the metastable phase exhibits structural features similar to both amorphous and crystalline phases, , we chose κ values of 0.15 and 0.20 W/mK, which are intermediate values between 0.13 and 0.24 W/mK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such highly oriented features can be often observed in other layered tellurides. 43,44 A fast Fourier transformed (FFT) image shows spots along the out-of-plane direction, and the spot location was found to correspond to the (002) lattice spacing. These TEM results strongly support the potential of the large area growth of a MoTe 2 film by sputtering followed by optimized annealing.…”
Section: (B) Ismentioning
confidence: 99%